Efecto del tratamiento combinado con esteroides y ciclofosfamida sobre la mortalidad en intoxicación por paraquat. Meta análisis (2010)
ABSTRACT: Objective: systematic review to update evidence about whether the combined use of cyclophosphamide and intravenous glucocorticoids in adults with moderate to severe paraquat poisoning compared to conventional treatment, decreases the 30-day mortality rate in randomized and quasi-randomized controlled trials.Methods: search in electronic databases, abstracts from scientific conferences, references in relevant articles and contact with experts. Randomized and quasi-randomized controlled trials on adult paraquat poisoning were included comparing this regimen with conventional treatment. Full text reviewed if they met inclusion criteria. Duplicate trials excluded. Two separate authors extracted data and double tool entrance data from ReviewManager® 5 was used. Results: three randomized controlled trials identified (n=93) with acceptable methodology for meta-analysis. Intervention group mortality was 25% (12/47) vs. 67% (31/46) for control group and risk-ratio 0.35 (IC95%: 0.21-0.61). Cochran ́s Q test p= 0.93 and I2 0% suggesting homogeneity. According to this, a fixed effects model was used. Sensitivity analysis performed with random-effect yielding similar results to fixed effects model suggesting robust results. Therapy adverse events were leukopenia with no infections (37%), acne, hair loss and hyperglycemia. Small number of studies, so the power to detect publication bias was not reached. Conclusions: results suggest immunosuppressive therapy is effective in decreasing mortality risk in adults with moderate to severe paraquat poisoning. Use of this therapy regimen is recommended.